Prospects for γδ T cells and chimeric antigen receptor γδ T cells in cancer immunotherapy - Lu Wang; Jiaqi Li; Yaping Xuan; Jinrui Zhang; Xiao Wang; Wei Hu; Wei Hu; Wei Hu; Lei Xiu (Frontiers in Immunology)
γδ T cells, a type of specialized T cell, differ from alpha-beta T cells due to the presence of γ and δ chain surface T cell receptors. These receptors allow them to directly recognize and bind antigenic molecules without the requirement of attachment to MHC or APC antigen presentation. Given their intrinsic properties and functional versatility, γδ T cells are under intensive investigation as carriers for chimeric antigen receptor (CAR) in the context of cancer therapy. In this regard, γδ CAR-T cells have demonstrated great potential to overcome the limitations of antigen recognition with the help of dual antigen identification mechanisms. However, there are still technological challenges that need to be addressed. This discussion focuses on the research status and future development prospects of γδ T cells and γδ CAR-T cells, aiming to provide valuable insights for the follow-up research and practical application of γδ CAR-T cells.